Persepsi Masyarakat Batang Terhadap Festival Anggaran Pemerintah Kabupaten Batang (Studi Kasus Masyarakat Kecamatan Batang) - Aziz, Abdul; ., Yuwanto; Manar, Dzunuwanus Ghulam (Journal of Politic and Government Studies, 2017)
Abstract. Regional autonomy in Indonesia is the right, authority and obligation of autonomous regions to regulate their own affairs and interests, Including in the preparation of Local Government Budgets becomes the authority for local government. However, the existence of such authority also provides opportunities for irregularities in regional budgeting that can threaten the realization of good governance therefore, in the budgeting process it is necessary to apply principles of transparency, accountability and participation. Budget Festival Government of Batang Regency is one effort to realize the principle of good governance. Therefore, this research tries to find out the perception of society to the implementation of Budget Festival activity and also the benefit of the activity.Samples taken in the research were 100 respondents spread in Batang, Regency Of Batang, Central Java. Samples were drawn using simple random sampling technique. The data were collected by questionnaire, observation and interview. The data that has been collected is then analyzed using descriptive statistical techniques.The results show that 58% of respondents interpreter the Budget Festival as a means of providing information on the use of Local Government Budget, and by 22% interpreted the Budget Festival as a vehicle for participation, 8% of respondents rate as an activity to increase the popularity of Batang regency, 4% rate as a regular event and 8% respondent do not know the meaning of the activity. From the research results also known that the Budget Festival can increase public knowledge of local government budget, increase community participation and prevent the occurrence of irregularities.Keywords: Regional autonomy, good governance, transparency, accountability, participation.